ZIKIR MEMAKAI BIJI TASBIH DALAM PERSPEKTIF LIVING HADIS - Muhammad AlFatih Suryadilaga (Jurnal Dialog, 2017)
Remembrance and prayer is something that is encouraged in Islam. Evidence of human devotion to his Lord is always given to Allah. In the everyday world, not least every Muslim after the five daily prayers constantly zikr. In the culture of remembrance in Indonesia is not only done individually but also together or in groups both small and large quantities, such as istighasah made in large numbers by reading verses of the Qur’an and other wird/zikir. Recitation has become a culture among Indonesia’s Muslim population. Their use of the tasbih in doing zikir in its history is the command of the Prophet. Where at the time of the Prophet. implementation of remembrance wear such devices rocks. Along with the times, the tool change like beads made of various materials such as wood, beads, glass, and so on. Even now found digital rosary is not just their number amounted to 100 pieces but could be in a matter of tens of thousands or even hundreds of thousands. These beads specifications tailored to the interests of each user tasbih, where in everyday life after prayer beads then simply wear size 99 or smaller pieces 33 pieces. However, if the readings of remembrance will be read very many uses digital tasbih.